Power losses on grain oriented and non-grain oriented materials using epstein test for electrical machine design - Ismail, Daut, Prof. Dr.; Anayet, Karim; Mohd Asri, Jusoh; Gomesh Nair, Shasidharan; Syatirah, Mohd Noor; Mohd Muzhar, Ahmad Tajuddin (ACTA Press, 2010)
Link to publisher's homepage at http://www.actapress.com/